2017
DOI: 10.1021/acsnano.7b03519
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Imaging of Human Mesenchymal Stem Cells Labeled with Prussian Blue–Poly(l-lysine) Nanocomplexes

Abstract: Acoustic imaging is affordable and accessible without ionizing radiation. Photoacoustic imaging increases the contrast of traditional ultrasound and can offer good spatial resolution when used at high frequencies with excellent temporal resolution. Prussian blue nanoparticles (PBNPs) are an emerging photoacoustic contrast agent with strong optical absorption in the near-infrared region. In this study, we developed a simple and efficient method to label human mesenchymal stem cells (hMSCs) with PBNPs and imaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
104
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 75 publications
(134 reference statements)
5
104
0
Order By: Relevance
“…The C‐HSA‐BOPx‐IR825 NP was employed to test the pH in the tumor region by both ratiometric PA and fluorescence imaging. Other NIR dyes, including naphthalocyanines, phthalocyanine, croconine, squaraine, and Prussian blue, can also serve as PA contrast agents.…”
Section: Organic Contrast Agentssupporting
confidence: 81%
“…The C‐HSA‐BOPx‐IR825 NP was employed to test the pH in the tumor region by both ratiometric PA and fluorescence imaging. Other NIR dyes, including naphthalocyanines, phthalocyanine, croconine, squaraine, and Prussian blue, can also serve as PA contrast agents.…”
Section: Organic Contrast Agentssupporting
confidence: 81%
“…PAI combines the advantages of pure optical imaging and pure ultrasound imaging, providing high‐resolution and high‐contrast tissue imaging. Kim et al recently reported the long‐term (up to 14 d) and highly sensitive (200 cells mL −1 in vivo) PAI of human MSCs labeled with Prussian‐blue–poly( l ‐lysine) nanocomplexes.…”
Section: Nanomaterials For Nsc Imagingmentioning
confidence: 99%
“…19 In addition, PB-poly-L-lysine (PLL) nanocomplex has been used as a highly efficient photoacoustic contrast agent for stem cells labelling and tracking. 20 However, these nano-drug delivery systems based on bare PB NPs showed the short systemic circulation time, which extremely limited the drug accumulation at tumor sites. 21 Meanwhile, the weak evading ability from macrophage uptake and strong blood clearance preference also reduced the therapy efficiency.…”
Section: Introductionmentioning
confidence: 99%